Identification of microRNAs and their mRNA targets during soybean nodule development: functional analysis of the role of miR393j‐3p in soybean nodulation. Issue 3 (17th March 2015) - Yan, Zhe; Hossain, Md Shakhawat; Arikit, Siwaret; Valdés‐López, Oswaldo; Zhai, Jixian; Wang, Jun; Libault, Marc; Ji, Tieming; Qiu, Lijuan; Meyers, Blake C.; Stacey, Gary
Summary Plant microRNAs (miRNAs) play important regulatory roles in a number of developmental processes. The present work investigated the roles of miRNAs during nodule development in the crop legume soybean (Glycine max). Fifteen soybean small RNA libraries were sequenced from different stages of nodule development, including young nodules, mature nodules and senescent nodules. In order to identify the regulatory targets of the miRNAs, five parallel analysis of RNA ends (PARE) libraries were also sequenced from the same stages of nodule development. Sequencing identified 284 miRNAs, including 178 novel soybean miRNAs. Analysis of miRNA abundance identified 139 miRNAs whose expression was significantly regulated during nodule development, including 12 miRNAs whose expression changed > 10‐fold. Analysis of the PARE libraries identified 533 miRNA targets, including three nodulation‐related genes and eight nodule‐specific genes. miR393j‐3p was selected for detailed analysis as its expression was significantly regulated during nodule formation, and it targeted a nodulin gene, Early Nodulin 93 (ENOD93). Strong, ectopic expression of miR393j‐3p, as well as RNAi silencing of ENOD93 expression, significantly reduced nodule formation. The data indicate that miR393j‐3p regulation of ENOD93 mRNA abundance is a key control point for soybean nodule formation.